Carbon isotopes in the ocean model of the Community Earth System Model (CESM1) - Jahn, A.; Lindsay, K.; Giraud, X.; Gruber, N.; Otto-Bliesner, B. L.; Liu, Z.; Brady, E. C. (Geoscientific Model Development, 2015)
Carbon isotopes in the ocean are frequently used as paleoclimate proxies and as present-day geochemical ocean tracers. In order to allow a more direct comparison of climate model results with this large and currently underutilized data set, we added a carbon isotope module to the ocean model of the Community Earth System Model (CESM), containing the cycling of the stable isotope 13C and the radioactive isotope 14C. We implemented the 14C tracer in two ways: in the "abiotic" case, the 14C tracer is only subject to air–sea gas exchange, physical transport, and radioactive decay, while in the "biotic" version, the 14C additionally follows the 13C tracer through all biogeochemical and ecological processes. Thus, the abiotic 14C tracer can be run without the ecosystem module, requiring significantly fewer computational resources. The carbon isotope module calculates the carbon isotopic fractionation during gas exchange, photosynthesis, and calcium carbonate formation, while any subsequent biological process such as remineralization as well as any external inputs are assumed to occur without fractionation. Given the uncertainty associated with the biological fractionation during photosynthesis, we implemented and tested three parameterizations of different complexity. Compared to present-day observations, the model is able to simulate the oceanic 14C bomb uptake and the 13C Suess effect reasonably well compared to observations and other model studies. At the same time, the carbon isotopes reveal biases in the physical model, for example, too sluggish ventilation of the deep Pacific Ocean.